2016
DOI: 10.2106/jbjs.o.00706
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing Compared with Spica Casts for Isolated Femoral Fractures in Four and Five-Year-Old Children

Abstract: Preschool-age children (four to five years old) with an isolated femoral fracture have similar clinical and radiographic outcomes regardless of whether they are treated with immediate spica cast immobilization or IMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 23 publications
1
40
1
5
Order By: Relevance
“…We found minor differences in the mean coronal and sagittal angulations between the ESIN and SPICA groups, consistent with the findings of Saseendar et al [10], Heffernan et al [24], and Ramo et al [26]. Two patients in the SPICA group showed unacceptable alignment at the time of union, one of whom was a 4-year-old boy with 20° varus and 30° anterior angulation, and another was a 4.5-year-old boy with 30° varus and 25° anterior angulation; both patients also showed limb length discrepancy at the time of union (2-and 2.5-cm shortening, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…We found minor differences in the mean coronal and sagittal angulations between the ESIN and SPICA groups, consistent with the findings of Saseendar et al [10], Heffernan et al [24], and Ramo et al [26]. Two patients in the SPICA group showed unacceptable alignment at the time of union, one of whom was a 4-year-old boy with 20° varus and 30° anterior angulation, and another was a 4.5-year-old boy with 30° varus and 25° anterior angulation; both patients also showed limb length discrepancy at the time of union (2-and 2.5-cm shortening, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…The first step of our study was the evaluation of our patient population in regard to comparability with cohorts investigated in the recent literature. Like others, we found boys to be predominantly affected by isolated femoral fractures, and simple falls were the most common cause [3,17,24]. Child abuse was only suspected in 4.8 % of cases in the present study; this finding was in contrast to that of Rewers et al, who reported suspected child abuse as the reason of femoral fracture in 14.8 % of all cases [26].…”
Section: Discussioncontrasting
confidence: 78%
“…ESIN resulted in better fracture length and alignment, as well as earlier weight-bearing and return to nursery. 6 Finally, Ramo et al 11 reported similar rates of unplanned revision surgery in their cohort of 262 patients, with 4% in both groups returning to the operating room. Although these studies are important additions to the literature on this topic, they may be underpowered to detect statistically notable differences in the revision surgery rate.…”
Section: Discussionmentioning
confidence: 85%
“…Potential advantages of ESIN are quicker mobilization and return to activities, more stable fixation with possibly less malunion and greater ease of care. 6 , 8 , 10 , 11 Disadvantages are that it is a more invasive surgical procedure that may require a second operation for implant removal and that the estimated immediate costs are higher compared with spica. 9 , 12 , 13 Spica casting is less invasive and has a lower estimated immediate cost.…”
Section: Discussionmentioning
confidence: 99%